REASONING ON THE HISTORY OF THE STUDY OF KINSHIP TERMS IN UZBEK AND ENGLISH LANGUAGES - Vasila Vakhobovna Karimova; Munisa Karimova (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals mainly with a brief history of the study of the system of kinship terms on the materials of the Uzbek and English languages.